Complexo da Estacao Ferroviaria de Jundiai e Complexo FEPASA: comparative analysis of heritage as a cultural resource for tourism - Silva, Milena Meira [UNESP] (Gobierno Canarias, Consejeria Educacion Cultura & Deportes, 2018)
This study proposes a comparative analysis of conservation practices and uses between the Complexo da Estacao Ferroviaria de Jundiai and Complexo FEPASA, in the municipality of Jundiai-SP, Brazil. Specifically, we seek to detail existing protection of these railway assets (CONDEPHAAT at state level and IPHAN at national level), as well as preservation actions adopted by the municipality. Uses, state conservation and tourist services have also been identified, based on Murta and Albano (1995), as well as the Geographic Information System (GIS) tool. The analysis by means of GIS technology contributes to the inventory of those assets and presents itself as a viable alternative to the different planning stages. The result of the study shows that the Complexo FEPASA offers greater tourist potential than the Complexo da Estacao Ferroviaria de Jundiai, considering its different uses and management at the present time.
Keywords: Industrial heritage; Railway complex; Preservation of the heritage; Industrial tourism; GIS